2D-3D Computations of a Vertical Axis Wind Turbine Flow Field: Modeling Issues and Physical Interpretations. (June 2019) - Franchina, N.; Persico, G.; Savini, M.
Abstract: This paper presents the results of a numerical investigation on the flow field past a Vertical Axis Wind Turbine at different operating conditions. Several numerical issues are considered, including the extension of the domain, the class of boundary conditions assigned, the space and time resolution, and the numerical accuracy in the resolution of the equations. The inlet boundary condition and the physical position where it is assigned, as well as appropriate far field conditions, are shown to be crucial for the reliability of the computed turbine performance. The use of proper boundary conditions and numerical settings allows performing three-dimensional unsteady calculations of VAWT aerodynamics with a technically-acceptable computational cost. The conclusions obtained are strengthened by a detailed comparison with a large data-base of experiments available for the turbine under consideration, that include both performance and time-resolved velocity measurements in the wake. The resulting flow model is then used to run time-accurate two-dimensional (2D) and three-dimensional (3D) simulations of the flow around the turbine. This set of simulations is exploited in combination to dedicated studies on the unsteady profile aerodynamics as well as detailed three-dimensional measurements in the wake to provide consistent physical interpretations of the computed flow fields. Highlights: 2D-3D computations of a VAWT using proper computational grids, boundary conditions and numerical settings. Performance prediction of a VAWT through 2D-3D modeling. Physical interpretation of complex three dimensional vortical structures with comparison to a large experiments data-base.